2007
DOI: 10.1136/jcp.2007.049684
|View full text |Cite
|
Sign up to set email alerts
|

Value of multicolour fluorescence in situ hybridisation (UroVysion) in the differential diagnosis of flat urothelial lesions

Abstract: UroVysion fluorescence in situ hybridisation is a valuable tool for the detection of genetically unstable flat urothelial lesions, and can help to resolve difficult cases, particularly the differential diagnosis of reactive atypia and dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 40 publications
8
25
0
1
Order By: Relevance
“…More extensive investigation of CIS may reveal clinical circumstances for which this method is particularly useful. For example, applying the UV technique to paraffin-embedded biopsy samples, Schwarz and colleagues [151] found polysomy of one or more chromosomes in 91% of CIS cases (30/33) and deletion of 9p21 in 74% (22/31), leading the authors to propose this technique as an aid for resolution of histologically challenging biopsies as well as cytologic samples.…”
Section: Molecular Markers For Early Detection Of Tccmentioning
confidence: 96%
“…More extensive investigation of CIS may reveal clinical circumstances for which this method is particularly useful. For example, applying the UV technique to paraffin-embedded biopsy samples, Schwarz and colleagues [151] found polysomy of one or more chromosomes in 91% of CIS cases (30/33) and deletion of 9p21 in 74% (22/31), leading the authors to propose this technique as an aid for resolution of histologically challenging biopsies as well as cytologic samples.…”
Section: Molecular Markers For Early Detection Of Tccmentioning
confidence: 96%
“…TMAs can also be constructed from flat urothelial lesions. Schwarz et al [40] constructed a TMA containing 29 samples of normal urothelium and 86 flat urothelial lesions (hyperplasia, reactive atypia, dysplasia and carcinoma in situ) ( Figure 1). Multicolour FISH using the Urovysion † test showed that polysomy and/or deletions of the chromosomal region 9p21 could be demonstrated in 50Á90% of cells in urothelial dysplasias and carcinoma in situ, but only infrequently in urothelial hyperplasias, reactive lesions or normal urothelium.…”
Section: Fluorescence In Situ Studies Using Tissue Microarraysmentioning
confidence: 99%
“…Insbesondere wenn es sich um das Monitoring von Patienten, die eine High-grade-Läsion hatten handelt oder solche, die dafür ein Risiko haben, hat sich das FISHunterstützte Monitoring dieser Patienten bewährt [3]. Diese Daten werden auch durch den Einsatz der UroVysion®-Probe am Schnittpräparat belegt [10] [6]). Während in den bisherigen Abschnitten betont wurde, wo der Einsatz von UroVysion® sinnvoll ist, sei abschließend noch ergänzt, dass bei eindeutig positiver Zytologie eine FISH in der bisherigen Zusammensetzung der Sonden keine Zusatzinformation bringt.…”
Section: Indikationen Mit Algorithmus Für Die Praxisunclassified